MINAT MAHASISWA PENDIDIKAN EKONOMI PERGURUAN TINGGI FKIP UNIVERSITAS TANJUNGPURA DALAM BERWIRAUSAHA - Susi, Susi; Syahrudin, Husni; Basri, Muhammad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Interest in Entrepreneurial Students at Tanjung Pura University is the title of the survey. Finding and contrasting factors that affect students at FKIP UNTAN who are pursuing business education is the goal of this study. Distribute surveys and collect data using the SPSS approach for quantitative descriptive multiple linear regression, ttests, and f-tests. Students from the 2020 regular A class and the 2019 business education class made up the study's population. A sample size of 60 was used. The findings demonstrated that factors and opportunities related to the family environment significantly influenced the entrepreneurship interest of FKIP UNTAN economics students. The survey's findings show that 83.3% of students are interested in starting a business, while 16.7% aren't at all interested. Strong interest thus fuels the urge to launch a business, allowing FKIP UNTAN to achieve policy achievements in entrepreneurship among students.